MEDICAL AND PREVENTIVE MEASURES WHEN TREATING THE FUNDAMENTAL DENTAL DISEASES IN PREGNANT WOMEN WITH DIABETES MELLITUS - Ye. I. Alexandrov (Кубанский научный медицинский вестник, 2016)
According to research statistics, the natural connection was established between diabetes and pathogenesis of the fundamental dental diseases. Disorders occurring in diabetes mellitus result in abnormal pregnancy and substantial deterioration of teeth and periodontal health. The rate of such dental pathology, as periodontal diseases and dental caries, increases and these diseases become more in diabetic pregnancy. Developing new methods of prevention and treatment of periodontal diseases and dental caries in pregnant women with diabetes mellitus remain an open problem in the modern stomatology.